Physico-chemical, mechanical and histological characteristics on rumen and reticulum of sheep submitted to different techniques of retanning - Cerquetani, Daniel de Almeida; Souza, Maria Luiza Rodrigues de; Gasparino, Eliane; Dourado, Doroty Mesquita; Silva, Stefania Caroline Claudino da; Roldi, Gabriel; Braccini, Graciela Lucca; Lala, Bruno (Medicina Veterinária, 2019)
The objective was to evaluate the physicochemical, mechanical and histological characteristics on rumen and reticulum of sheep submitted to different retanning techniques. Twenty rumens and reticulum were tanned with chrome and retanned with different tannins (Treatment1 = chrome; Treatment2 = vegetable; Treatment3 = synthetic and Treatment4 = vegetable + synthetic). Tanned samples of rumens and reticulum were extracted to evaluate the arrangement of fibers, and submitted for determination of chrome oxide, substances extractable with dichloromethane, pH value and difference figure of aqueous extract. Thickness, traction resistance, elongation and progressive tearing were measured. Retanning with chrome provided greater traction resistance (3.47 N mm-2), elongation (92.76%) and progressive tearing (28.81 N mm-1). Retanning with synthetic tannins showed less traction resistance (2.68 N mm-2) and increased thickness (1.25 mm). The rumen presented better results for tensile strength and progressive tearing. Elasticity results did not differ for both rumen and reticulum. Both rumen and reticulum retanned with chrome salts showed higher levels of chrome oxide and substances extractable by Dichloromethane (34.2%). Therefore, the best results were obtained for rumen retanned with chrome salts.